2023
DOI: 10.3390/ma16083216
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Enhanced Nanocrystal Infrared Photodetectors

Abstract: Low-dimensional nanomaterials are widely investigated in infrared photodetectors (PDs) due to their excellent optical and electrical properties. To further improve the PDs property like quantum efficiency, metallic microstructures are commonly used, which could squeeze light into sub-diffraction volumes for enhanced absorption through surface plasma exciton resonance effects. In recent years, plasmonic enhanced nanocrystal infrared PDs have shown excellent performance and attracted much research interest. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…The strategies to enhance hot carrier generation, carrier injection, separation, and transportation are discussed in detail. Although efficient utilization of plasmon-induced hot carriers is still challenging, their applications in photocatalysis, photovoltaics, photodetectors, and ultrafast optical modulations are emerging and highly demanded [196,[282][283][284][285] . Thus far, numerous efforts have been devoted to the hot carrier utilization in semiconductors.…”
Section: Hot-carrier-based Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategies to enhance hot carrier generation, carrier injection, separation, and transportation are discussed in detail. Although efficient utilization of plasmon-induced hot carriers is still challenging, their applications in photocatalysis, photovoltaics, photodetectors, and ultrafast optical modulations are emerging and highly demanded [196,[282][283][284][285] . Thus far, numerous efforts have been devoted to the hot carrier utilization in semiconductors.…”
Section: Hot-carrier-based Applicationsmentioning
confidence: 99%
“…The maximum responsivity is about 8 nA/mW without bias. Since then, extensive plasmonic infrared photodetectors have been developed [273,284,[354][355][356] . For instance, Wen et al reported a near-infrared photodetector device by combining the randomly and densely packed Au nanostructures with ultrathin silicon nanohole coatings (Au-SiNH), as shown in Fig.…”
Section: Photodetectorsmentioning
confidence: 99%
“…The coupling to photonic structures is one of the most striking developments achieved. 5,6 With such structures, light−matter coupling is no longer driven only by material properties but rather by the geometrical aspects of the cavity. Beyond boosting the infrared (IR) absorption magnitude, 7−10 such approaches have been relevant to generating new functionalities, including an actively reconfigurable photoresponse.…”
mentioning
confidence: 99%
“…Thanks to this progress, the focus has evolved toward integrating these infrared NCs into complex devices far beyond the simple sandwiching of an absorbing layer between charge transporting/blocking layers. The coupling to photonic structures is one of the most striking developments achieved. , With such structures, light–matter coupling is no longer driven only by material properties but rather by the geometrical aspects of the cavity. Beyond boosting the infrared (IR) absorption magnitude, such approaches have been relevant to generating new functionalities, including an actively reconfigurable photoresponse. , However, the most striking progress certainly relates to the transition from a single-pixel detector to a full infrared camera.…”
mentioning
confidence: 99%
“…Meanwhile, the Ebessen’s group has brought evidence that under certain conditions of resonance, the transmission of a subwavelength aperture can significantly exceed the value set by its filling factor. This pioneer work has later been expanded toward the field of extraordinary optical transmission and plasmonic nanohole arrays. , Here, we explore the design of a resonant metallic grid offering an alternative to TCO as a transparent electrode in the infrared. The grating is designed so that multiple resonances arise, hence allowing a broadband enhancement of the infrared NC absorption.…”
mentioning
confidence: 99%